(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Theoretically, Islamic banks need to be more stable than traditional ones. Presumably, they share the profits as the obligations and securities. In practice, Islamic banks have assets with fixed income, and participate in the profits of the obligations. To achieve compliance with the Western system, they should be more similar to the capital adequacy and risk management practices between the organization of accounting control and audit of Islamic financial institutions, the Islamic Committee on Financial Services, the Islamic Development Bank and the Bank for International Settlements. Also affects the stability and availability of the size of the secondary market. Although the process of lending and investment analysis techniques may diverge from traditional Islamic approaches are based on similar analytical methods and techniques of accounting risk. In the end, the determining factor is the accuracy of the basic approaches of risk analysis related to specific products.